The responses of carotenoids in cyanobacteria anabaena cylindrica as potential bio-indicator for heavy metals detection - Saktis, Paul (EM International, 2016)
Heavy metals have detrimental effect on humans and other organisms, therefore continuous monitoring is required. The main objective of this experiment is to study the effects of single and combined toxicity response of Anabaena cylindrica towards three heavy metals- copper (Cu), cadmium (Cd) and lead (Pb). The cells from day 7 culture with approximately 2.36 × 106 cell/ mL were immobilized with 1% agarose in cuvettes. The exposures to various concentrations of heavy metals were then carried out. The effects of heavy metals on carotenoids, produced during photo oxidative stress were measured using spectrophotometer at λ = 450 nm. The results showed the cells responded to single heavy metal by the change of optical density (OD), while predominantly antagonistic effect was indicated on combined toxicity of heavy metals. The response of A. cylindrica to heavy metals showed the potential of the cyan bacteria to be utilized as bio-indicator for single and combined heavy metals detection in aquatic environment.